Strategi Optimalisasi Implementasi Digitalisasi Pengelolaan Zakat Sebagai Upaya Meningkatkan Transparansi Pada Baznas Provinsi Jambi - Agustian Rosa Fajri; Anzu Elvia Zahara; Muthmainnah Muthmainnah (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The implementation of online zakat payments by BAZNAS Jambi Province faced several challenges, including suboptimal use of the Simba application due to system errors. Additionally, there was a lack of public trust in online zakat payments, insufficient public literacy on the matter, and inadequate socialization and education from BAZNAS Jambi regarding the online payment process. This study used a qualitative descriptive approach, with data collection via interviews. To optimize digital zakat management, BAZNAS Jambi implemented a strategy involving both their website and the SIMBA system, offering two digital payment options: transfers and QRIS codes. They also pursued partnerships with companies and promoted zakat payments through social media platforms such as YouTube, TikTok, Facebook, Google Ads, Meta Ads, as well as TVRI and RRI television. However, there were challenges, including human resource limitations at BAZNAS Jambi, which resulted in delays when verifying factual data. Additionally, high IT operational costs limited the effectiveness of SIMBA and the website. The coordination issues, including both functional and institutional coordination, were also identified as significant problems. To address these challenges, BAZNAS Jambi has been working on solutions such as community education, socializing zakat management with the public and local government agencies (OPDs), and improving internal coordination.